2020
DOI: 10.3847/1538-4357/abb830
|View full text |Cite
|
Sign up to set email alerts
|

The ALMA Spectroscopic Survey Large Program: The Infrared Excess of z = 1.5–10 UV-selected Galaxies and the Implied High-redshift Star Formation History

Abstract: We make use of sensitive (9.3 μJy beam −1 rms) 1.2 mm continuum observations from the Atacama Large Millimeter/submillimeter Array (ALMA) Spectroscopic Survey in the Hubble Ultra-Deep Field (ASPECS) large program to probe dust-enshrouded star formation from 1362 Lyman-break galaxies spanning the redshift range z=1.5-10 (to ∼7-28 M e yr −1 at 4σ over the entire range). We find that the fraction of ALMA-detected galaxies in our z=1.5-10 samples increases steeply with stellar mass, with the detection fraction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
162
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(186 citation statements)
references
References 171 publications
22
162
2
Order By: Relevance
“…Our picture of the history of the cosmic star formation is consistent with previous results from long-wavelength (FIR to millimeter) surveys (e.g., Bourne et al 2017;Dunlop et al 2017;Hatsukade et al 2018;Dudzevičiūtė et al 2020), although most of those were limited to z  4. Hence, our results represent significant progress on our understanding of the prevalence of DSFGs during the first 1.5 billion years of the universe and complement the significant efforts carried out using UV/ optically selected galaxies (e.g., Bouwens et al 2020). The inferred SFRD is also in broad agreement with the most recent predictions from galaxy evolution models (like IllustrisTNG and SHARK; Pillepich et al 2018;Lagos et al 2020), which point toward a convergence between models and observations.…”
Section: % 25%supporting
confidence: 83%
See 2 more Smart Citations
“…Our picture of the history of the cosmic star formation is consistent with previous results from long-wavelength (FIR to millimeter) surveys (e.g., Bourne et al 2017;Dunlop et al 2017;Hatsukade et al 2018;Dudzevičiūtė et al 2020), although most of those were limited to z  4. Hence, our results represent significant progress on our understanding of the prevalence of DSFGs during the first 1.5 billion years of the universe and complement the significant efforts carried out using UV/ optically selected galaxies (e.g., Bouwens et al 2020). The inferred SFRD is also in broad agreement with the most recent predictions from galaxy evolution models (like IllustrisTNG and SHARK; Pillepich et al 2018;Lagos et al 2020), which point toward a convergence between models and observations.…”
Section: % 25%supporting
confidence: 83%
“…This suggests that the bulk (80%) of the star formation activity in the first billion years of the universe was not dust enshrouded. Given the massive nature of DSFGs, this drop-off of the obscured component is in line with the decreasing number of high-mass galaxies with increasing redshift (see also Dunlop et al 2017;Bouwens et al 2020).…”
Section: % 25%mentioning
confidence: 73%
See 1 more Smart Citation
“…Therefore, we opt not to include this further term into our estimates of the uncertainties. In support of the negligible contribution of cosmic variance, Magnelli et al (2020) and Bouwens et al (2020) find an excellent match between the stellar mass functions and cosmic SFR density in the ASPECS footprint and the ones inferred in the literature from much wider regions in different (physically disconnected) fields at any z0.5.…”
Section: ( ) ( )supporting
confidence: 75%
“…Theoretical studies have shown that the IRX-β scatter may depend on the type of dust, gas metallicity, star formation history (SFH), dust-star geometry, and stellar population age (Popping et al 2017;Safarzadeh et al 2017;Narayanan et al 2018;Schulz et al 2020). Observations have shown that the IRX-β relation varies with stellar mass (Bouwens et al 2016(Bouwens et al , 2020Reddy et al 2018;Fudamoto et al 2020), infrared (IR) luminosity (Buat et al 2012;Casey et al 2014), age (Siana et al 2009;Reddy et al 2010;Shivaei et al 2015), redshift (Capak et al 2015;Pannella et al 2015), and intrinsic β 0 (β for a dust-free system; Boquien et al 2012;Reddy et al 2018;Schulz et al 2020). These variations are linked to the diversity of galaxies' attenuation curves, seen in previous studies (e.g., Kriek & Conroy 2013;Scoville et al 2015;Battisti et al 2020).…”
Section: Introductionmentioning
confidence: 99%